Mechanical and acoustical properties of silver chloride from 100 K to 600 K. (2021) - Pandey, Krishna Kumar
Abstract: Silver Chloride (AgCl), which is having the FCC crystal structure is characterized in this research paper. On behalf of the mechanical properties, the different nine elastic constants have been calculated in the higher temperature region i.e. from 100 K to 600 K. For further characterizations of AgCl, the Acoustic wave such as ultrasonic wave is used to find its attenuation when it passes through AgCl along 〈1 1 1〉 crystallographic direction in both the modes of propagation i.e. longitudinal as well as shear from 100 K to 600 K. The Ultrasonic attenuation due to screw as well as due to edge dislocations has also been computed.